Environmental filtering and phylogenetic clustering correlate with the distribution patterns of cryptic protist species - Singer, David; Kosakyan, Anush; Seppey, Christophe V W; Pillonel, Amandine; Fernández, Leonardo D; Fontaneto, Diego; Mitchell, Edward A D; Lara, Enrique (Ecology, 2018)
The community composition of any group of organisms should theoretically be determined by a combination of assembly processes including resource partitioning, competition, environmental filtering, and phylogenetic legacy. Environmental DNA studies have revealed a huge diversity of protists in all environments, raising questions about the ecological significance of such diversity and the degree to which they obey to the same rules as macroscopic organisms. The fast-growing cultivable protist species on which hypotheses are usually experimentally tested represent only a minority of the protist diversity. Addressing these questions for the lesser known majority can only be inferred through observational studies. We conducted an environmental DNA survey of the genus Nebela, a group of closely related testate (shelled) amoeba species, in different habitats within Sphagnum-dominated peatlands. Identification based on the mitochondrial cytochrome c oxidase 1 gene, allowed species-level resolution as well as phylogenetic reconstruction. Community composition varied strongly across habitats and associated environmental gradients. Species showed little overlap in their realized niche, suggesting resource partitioning, and a strong influence of environmental filtering driving community composition. Furthermore, phylogenetic clustering was observed in the most nitrogen-poor samples, supporting phylogenetic inheritance of adaptations in the group of N. guttata. This study showed that the studied free-living unicellular eukaryotes follow to community assembly rules similar to those known to determine plant and animal communities; the same may be true for much of the huge functional and taxonomic diversity of protists.
Keywords: ekologie; rostliny; Animals; Plants; ekosystém; rašeliníky; Phylogeny; Ecosystem; Sphagnopsida; Ecology; niche partitioning; phylogenetic clustering/over-dispersion; zvířata; fylogeneze; environmental filtering; Nearest Taxon Index; uncultivable protists; Sphagnum-dominated peatlands